Diflunisal Attenuates Virulence Factor Gene Regulation and Phenotypes in Staphylococcus aureus - Liana C. Chan; Mihyun Park; Hong K. Lee; Siyang Chaili; Yan Q. Xiong; Arnold S. Bayer; Richard A. Proctor; Michael R. Yeaman (Antibiotics, 2023)
Virulence factor expression is integral to pathogenicity of Staphylococcus aureus. We previously demonstrated that aspirin, through its major metabolite, salicylic acid (SAL), modulates S. aureus virulence phenotypes in vitro and in vivo. We compared salicylate metabolites and a structural analogue for their ability to modulate S. aureus virulence factor expression and phenotypes: (i) acetylsalicylic acid (ASA, aspirin); (ii) ASA metabolites, salicylic acid (SAL), gentisic acid (GTA) and salicyluric acid (SUA); or (iii) diflunisal (DIF), a SAL structural analogue. None of these compounds altered the growth rate of any strain tested. ASA and its metabolites SAL, GTA and SUA moderately impaired hemolysis and proteolysis phenotypes in multiple S. aureus strain backgrounds and their respective deletion mutants. Only DIF significantly inhibited these virulence phenotypes in all strains. The kinetic profiles of ASA, SAL or DIF on expression of hla (alpha hemolysin), sspA (V8 protease) and their regulators (sigB, sarA, agr (RNAIII)) were assessed in two prototypic strain backgrounds: SH1000 (methicillin-sensitive S. aureus; MSSA) and LAC-USA300 (methicillin-resistant S. aureus; MRSA). DIF induced sigB expression which is coincident with the significant inhibition of RNAIII expression in both strains and precedes significant reductions in hla and sspA expression. The inhibited expression of these genes within 2 h resulted in the durable suppression of hemolysis and proteolysis phenotypes. These results indicate that DIF modulates the expression of key virulence factors in S. aureus via a coordinated impact on their relevant regulons and target effector genes. This strategy may hold opportunities to develop novel antivirulence strategies to address the ongoing challenge of antibiotic-resistant S. aureus.